Visual acuity analysis on the phakic lenses implantation in high myopia - Santos, Vanessa (2022)
Introduction – Intraocular phakic lens implantation surgery has been progressively preferred to laser surgery in the treatment of high myopia. Visual acuity (AV) pre and post-refractive implant surgery have been compared, showing that this method is more effective in the improvement of vision in high myopia. Methods – Seventy eyes belonging to 41 patients with high myopia were analyzed retrospectively. The age of the patients ranged from 20 to 50 years and they all had refractive implant surgery between 2009 and 2012. Results – One-day post-surgery, 42.86% of the sample had an improvement in visual acuity, 34.29% remained unchanged and 22.85% worsened. A generalized increase in the quality of vision was observed after 30 days. 64.29% scored 10/10 in visual acuity, 24.29% scored between 7/10 and 9/10, and 11.42% between 4/10 and 6/10. Conclusion – The effectiveness of this surgical technique was proved, showing an improvement in visual acuity in 52.86% of the sample.